Problematika nusyuz perempuan pada era masa kini - Azizah, Firly Kamilatul (Maliki Interdisciplinary Journal, 2025)
In Islam, the term nusyuz is used to refer to a disobedient woman. A nusyuz woman is a wife who is disobedient to her husband and violates her obligations in marriage. This behavior is categorized as a major sin and can have fatal consequences for the woman in question, both in this world and in the hereafter. The concept of disobedience is discussed in several verses of the Quran, such as in Surah An-Nisa’ verses 34 and 128, which are mentioned in this article. There are several factors that can lead a woman to fall into the category of nusyuz, such as: lack of religious understanding, negative environmental influences, selfishness and arrogance, incompatibility with her husband, and mental disorders. However, Islam also provides solutions to address a disobedient woman, namely: counseling, ceasing sexual relations, and requesting divorce if all efforts made fail to change the disobedient woman’s behavior.